Screening drug effects in patient‐derived cancer cells links organoid responses to genome alterations - Jabs, Julia; Park, Jeongbin; Jechow, Katharina; Kleinheinz, Kortine; Schneider, Marc; Meister, Michael; Spaich, Saskia; Sütterlin, Marc; Schlesner, Matthias; Eils, Roland; Conrad, Christian (Molecular systems biology, 2017)
Cancer drug screening in patient‐derived cells holds great promise for personalized oncology and drug discovery but lacks standardization. Whether cells are cultured as conventional monolayer or advanced, matrix‐dependent organoid cultures influences drug effects and thereby drug selection and clinical success. To precisely compare drug profiles in differently cultured primary cells, we developed DeathPro, an automated microscopy‐based assay to resolve drug‐induced cell death and proliferation inhibition. Using DeathPro, we screened cells from ovarian cancer patients in monolayer or organoid culture with clinically relevant drugs. Drug‐induced growth arrest and efficacy of cytostatic drugs differed between the two culture systems. Interestingly, drug effects in organoids were more diverse and had lower therapeutic potential. Genomic analysis revealed novel links between drug sensitivity and DNA repair deficiency in organoids that were undetectable in monolayers. Thus, our results highlight the dependency of cytostatic drugs and pharmacogenomic associations on culture systems, and guide culture selection for drug tests. Synopsis: DeathPro, an automated microscopy‐based assay resolves cell death and proliferation inhibition in 2D and 3D cultures. Drug screens using DeathPro provide insights into the impact of culture systems on drug effects and their links to genomic features. DeathPro resolves cytotoxic and cytostatic effects in drug screens with patient‐derived ovarian and lung cancer cells, organoids and co‐cultures with fibroblasts.Drug responses in cancer organoids are more diverse than in 2D cultured cells.Cytostatic drugs depend on culture systems, cytotoxic effects are independent of the culture format.Genomic analysis of cancer patients links DNA repair deficiency to drug sensitivity in organoids.